Use of perfluorocarbon in the culture of Saccharomyces cerevisiae - Elibol, M (Chapman Hall Ltd, 1996)
The growth of Saccharomyces cerevisiae was enhanced by using perfluorocarbon (PFC) while it was inhibited by pluronic F-68 alone. The use of 15% (v/v) PFC resulted in almost twice as much biomass concentration compared to the control. The inclusion of PFC emulsion in the culture medium also increased the maximum biomass concentration, but not as much as in the case of pure PFC.
Keywords: Immobilized Cells; Oxygen; Perfluorochemicals; Model